Time differentiation of correction actions retrospective by a person - Plokhikh, Viktor V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article deals with the human ability to differentiate and localize the retrospective of actions kept in short-term memory considering their temporal characteristics. The study is aimed at experimental determination of accuracy characteristics of temporal locality of events, different by the importance in the operative retrospective of correction actions, by men and women. The study sample involved 37 male and 37 female students divided into two groups. The surveyed performed correction tasks with a number of figures and letters. It has been found that time differentiation of the retrospective of correction actions and localization of events in the past, whose importance is not assessed in advance, is performed by a person relying on famous time references and the bonds between the sequence of events kept in short-term memory. The relative error of time localization of events in the retrospective of correction actions is bigger than the error of differentiation of time references. It has been revealed that the error of time differentiation of events of the retrospective of correctionactions is predominantly less in men compared to women.
Keywords: time differentiation; retrospective of actions; duration; sequence; short-term memory; reproduction of time intervals